(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2009)
The present study aimed to investigate the effects of earning and losing points contingent on the use of verbal tenses in sentence construction. In the experiment, 101 students were exposed to a computerized task in which sentences were constructed by selecting one of six different verbal tenses. In the experimental phase, and in different participant groups, the use of either Imperfect Past or Future was followed by the maintenance of points, the earning of a higher vs. a lower number of points, or the loss of a higher vs. a lower number of points relative to the use of any of the other five available verbal tenses. Results showed that the contingencies involving earning points (vs. the maintenance of points) and maintenance of points (vs. loss of points) generally produced greater reinforcing effects on the use of verbal tenses than the contingencies involving earning and losing points with higher vs. lower magnitude, particularly with respect to the Future tense. The present procedure describes alternative methods of investigating the effects of potentially aversive contingencies on human verbal behavior.